Revenues and expenditures of the state and local budgets in Ukraine in peacetime and under martial law: regulatory and legal provisions - Vorotina, Nataliia; Tykhonova, Olena; Poliak-Sverhun, Mariana; Cherniaieva, Olena (Jurnal Cita Hukum, 2024)
Martial law dictates the need to guarantee the proper level of execution of the state and local budgets, as well as to identify and attract additional sources of income and implement a rational and economical concept of expenditures. The level of coherence and efficiency of interaction between participants in the budgeting process determines the possibility of maintaining financial stability and avoiding macroeconomic imbalances. This article analyses Ukraine's budgetary sphere's regulatory revenues and expenditures during peacetime and wartime. The study involved general scientific methods, including analysis, synthesis, comparison, abstraction, specification, and generalisation. This research analyses the current state of regulatory and legal support of the state and local budgets. It outlines the concept of budgetary resource management in wartime. The author has found that the realities of wartime have led to some changes regarding filling budgets and forming expenditures. The study identified signs of budget deficit and specific issues that arise in contrast to peacetime processes. The author analyzed the indicators of the consolidated budget for pre-war and wartime and studied the vector of financial budget differentiation by sectors and programs. It is determined that the share of expenditures of the State Budget of Ukraine is focused on ensuring Ukraine's defence capability, which is dictated by wartime. The author has outlined the specific features of forming the local and State budgets during wartime, and the main issues of this process have been highlighted. In addition, the author formulated the main priority areas of optimisation in budgeting during wartime and in the context of further socio-economic development.